Factors that Influence the Work Interest of Prospective Undergraduate Education in Industry - Agung Widiyantoro; Putu Sudira; Rabiman Rabiman; Yayan Adrianova Eka Tuah (Jurnal Pendidikan dan Pengajaran, 2021)
The job market has a strong influence on the preferences of new graduates. One of these phenomena occurred at the Universitas Sarjanawiyata Tamansiswa Yogyakarta. Although the field occupied in this educational institution is pedagogic science, many graduates from this university are indifferent to the scientific family. This study aims to analyze the effect of work interest in Mechanical Engineering Education (MEE) industrial students on income, attention, willingness, family environment, and community environment. This study uses the ex-post-facto method. This study involved 82 students. The sampling technique used is simple random sampling with a questionnaire to collect data. The results showed that: (1) income expectations, attention, willingness, family environment, and community environment all had a positive and significant effect on interest in working in the industry; (2) income expectations have a positive and significant effect on job interest in the industry; (3) Attention has a positive and significant effect on interest in working in the industry, (4) willingness has a positive and significant effect on interest in working in the industry, (5) family environment has a positive and significant effect on interest in working in the industry, and (6) community environment has an effect positive and significant to work interest in the industry.